High-definition ultraviolet and infrared dual-blocking polyester protective film

CN122941145APending Publication Date: 2026-10-20温州强润新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611030228.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

涂层与PET基材之间的界面结合力有限,在长期使用中易出现附着力衰减、涂层划伤脱落等问题

Benefits of technology

[0049]1.本发明通过将苯并三唑紫外吸收基团、联萘酚手性中心与可聚合双键共价整合于同一分子骨架,形成双功能单体BZT-BN,避免了现有技术中紫外吸收剂、手性掺杂剂与可聚合单体等多组分物理混合体系固有的相分离、迁移析出与功能失配问题。BZT-BN的分子结构与PET/PBT基体具有良好的热力学相容性,在熔融共混过程中实现分子级均匀分散,既保证了紫外吸收基团和手性中心在薄膜厚度方向上的均匀分布,又避免了无机纳米粒子掺杂体系中团聚体形成的光散射中心,为实现高清度与双阻隔功能的统一提供了分子层面的结构保障。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a high-definition ultraviolet and infrared dual-barrier polyester protective film, belonging to the field of polymer functional materials technology. The film is prepared from PET resin, PBT resin, and the bifunctional monomer BZT-BN through melt blending, biaxial stretching, gradient cooling heat setting, and ultraviolet curing. The BZT-BN molecule covalently integrates the benzotriazole ultraviolet absorbing group, the binatol chiral center, and the polymerizable double bond into the same backbone. The thermotropic changes in hydrogen bonds within the benzotriazole molecule drive alterations in the helical twisting force of the binatol, achieving thermotropic reversible tuning of the cholesteric phase pitch. This invention achieves dual functions of ultraviolet absorption and infrared reflection with a single molecule, and locks the functional structure through covalent bonding and cross-linking networks. It possesses advantages such as high resolution and high light transmittance, dual ultraviolet and infrared blocking, zero-energy thermotropic self-adaptation, and excellent weather resistance, making it suitable for applications such as building energy-saving window films and automotive heat insulation films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer functional materials technology, and in particular to a high-resolution ultraviolet and infrared dual-barrier polyester protective film. Background Technology

[0002] Polyethylene terephthalate (PET) film has been widely used in architectural window films, automotive heat insulation films, electronic display protection, and photovoltaic module encapsulation due to its excellent mechanical properties, optical transparency, and dimensional stability. However, PET itself lacks effective blocking capabilities in the ultraviolet and near-infrared light regions, and PET films exhibit strong ultraviolet and infrared transmittance. To endow PET films with dual ultraviolet and infrared blocking capabilities, existing technologies mainly follow three routes, but each has its own insurmountable bottlenecks.

[0003] One method involves the doping of organic UV absorbers. This method physically blends small-molecule organic UV absorbers such as benzotriazoles and benzophenones with PET resin to form a film, utilizing the selective absorption of UV light by the absorber molecules to achieve UV blocking. Benzotriazole UV absorbers are widely used in various polymer materials due to their excellent performance; however, because of their relatively small molecular weight, they are prone to migration and volatilization during polymer processing and long-term use, resulting in poor lightfastness. Studies have shown that UV absorbers added to PET packaging materials pose a risk of migration and leaching during long-term storage. The migration behavior of light stabilizers UV-P and UV-234 in PET bottles has been reported in the literature. Migration not only leads to a continuous decline in the UV blocking performance of the film over time, but the precipitated absorber molecules may also affect the appearance quality and optical uniformity of the film. Furthermore, organic UV absorbers themselves undergo photodegradation under long-term UV irradiation, further exacerbating performance degradation.

[0004] The second method is inorganic nanoparticle doping. This method involves directly blending nanoparticles with infrared absorption or reflection functions (such as nano-ATO, ITO, cesium tungsten bronze, etc.) with PET resin, utilizing the selective absorption or reflection of near-infrared light by the nanoparticles to achieve infrared blocking. However, the specific surface area of ​​nano-inorganic powders is large, and they are prone to agglomeration without any dispersing agents or dispersion processes. These agglomerates in the finished film will significantly affect optical performance, such as producing high haze values. The agglomeration of inorganic nanoparticles in the PET matrix forms micron-sized aggregates, whose size is comparable to the wavelength of visible light, producing strong Mie scattering, resulting in a significant increase in film haze and a significant decrease in visible light transmittance. Adding functional microparticles to the raw materials often affects the optical performance of polyester films, and there is a difficult contradiction between increasing haze and infrared blocking requirements. At the same time, the infrared blocking of nanoparticles is based on free carrier absorption (Drude effect) or localized surface plasmon resonance absorption. The film itself will absorb infrared energy and heat up, generating secondary thermal radiation problems, affecting the heat insulation effect.

[0005] The third method is the cholesteric liquid crystal infrared reflective coating method. This method utilizes the one-dimensional chiral photonic crystal structure of cholesteric liquid crystals to selectively reflect near-infrared light in specific wavelengths through Bragg reflection. Previous studies have used a blade coating method to prepare cholesteric liquid crystal polymer films on PET substrates. This technique attaches the liquid crystal functional layer to the surface of the PET substrate in the form of a coating; the liquid crystal functional layer exists only on the film surface and is not distributed within the substrate. The interfacial adhesion between the coating and the PET substrate is limited, and problems such as adhesion attenuation and coating scratches and peeling are prone to occur during long-term use. Furthermore, the coating method requires additional coating equipment and process steps, increasing production costs and process complexity. More importantly, existing cholesteric liquid crystal infrared reflective coatings can only achieve static reflection in a fixed wavelength band and cannot automatically adjust the reflective performance according to changes in ambient temperature.

[0006] In summary, existing technologies for achieving dual UV and infrared blocking functionality in polyester films face multiple challenges, including the easy migration and photodegradation of organic UV absorbers, the tendency of inorganic nanoparticles to aggregate leading to increased haze, and the poor adhesion and inability to adaptively adjust cholesteric liquid crystal coatings. How to achieve efficient and long-lasting blocking in both UV and infrared bands while maintaining film clarity, and how to endow the film with the adaptive capability to automatically adjust its infrared reflectivity according to changes in ambient temperature, remains a pressing technical challenge. Summary of the Invention

[0007] The purpose of this invention is to address the shortcomings of existing technologies by proposing a high-definition ultraviolet and infrared dual-blocking polyester protective film.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: a high-definition ultraviolet-infrared dual-barrier polyester protective film, comprising the following components by weight: polyethylene terephthalate resin: 70-90 parts, polybutylene terephthalate resin: 5-20 parts, bifunctional monomer BZT-BN: 2-10 parts, heat stabilizer: 0.05-0.3 parts, antioxidant: 0.05-0.1 parts, and ultraviolet photoinitiator: 0.05-0.2 parts.

[0009] Preferably, the intrinsic viscosity of the polyethylene terephthalate resin is 0.65-0.75 dL / g.

[0010] Preferably, the intrinsic viscosity of the polybutylene terephthalate resin is 0.8-1.2 dL / g.

[0011] Preferably, the heat stabilizer is tris(2,4-di-tert-butylphenyl) phosphite.

[0012] Preferably, the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.

[0013] Preferably, the ultraviolet photoinitiator is the photoinitiator TPO.

[0014] Preferably, the preparation method of the bifunctional monomer BZT-BN includes the following steps:

[0015] (1) Under nitrogen protection, 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, alkyl diol and potassium carbonate were added to N,N-dimethylformamide. The mixture was heated to 70-80℃ with stirring and reacted for 4-6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filtrate was added to deionized water. The mixture was extracted three times with ethyl acetate. The organic phases were combined and washed once each with dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated brine. After drying with anhydrous sodium sulfate, the mixture was filtered, the solvent was removed by rotary evaporation, and the excess alkyl diol was recovered by vacuum distillation. The crude product was recrystallized in a mixed solvent of ethyl acetate / petroleum ether to obtain intermediate A. The chemical reaction equation is as follows:

[0016] This step is a nucleophilic substitution reaction. Potassium carbonate acts as an acid-binding agent, and the hydroxyl group at the end of the alkyl diol and the bromine atom in the benzyl bromide structure are substituted to generate aryl alkyl ethers. By using 8-12 times the excess of alkyl diol, the concentration of alkoxy anions in the system is much higher than the concentration of the monosubstituted product generated, thus kinetically suppressing the disubstituted side reaction.

[0017] (2) Under nitrogen protection, (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthylene was added to dichloromethane, stirred and cooled to 0℃, N,N'-dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP) were added, and the mixture was stirred and activated for 20-40 min. Then, a dichloromethane solution of intermediate A was added dropwise. After the addition was complete, the mixture was allowed to return to room temperature and stirred for 12-20 h. After the reaction was completed, the mixture was filtered, and the filtrate was washed once with dilute hydrochloric acid, saturated sodium bicarbonate solution, and saturated saline solution. After drying with anhydrous sodium sulfate, the mixture was filtered, and the solvent was removed by rotary evaporation. The crude product was purified by silica gel column chromatography using gradient elution to obtain intermediate B. The chemical reaction equation is as follows:

[0018] This step is a selective esterification reaction catalyzed by DCC / DMAP. DCC first adds to the carboxyl group of (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthyl to generate a highly active O-acylisourea intermediate. DMAP, acting as a nucleophilic catalyst, attacks the acyl carbon atom, transforming it into a more sterically hindered and highly active acyl-DMAP intermediate, simultaneously releasing dicyclohexylurea. The terminal aliphatic primary hydroxyl group of intermediate A nucleophilically attacks the acyl-DMAP intermediate, forming an ester bond through addition-elimination and regenerating DMAP. This process involves (R)- The molar ratio of 2,2'-bis(carboxymethyloxy)-1,1'-binaphthyl to intermediate A is strictly controlled at 2:1. The excess dicarboxylic acid ensures that each dicarboxylic acid reacts with only one intermediate A, avoiding the esterification byproduct of one dicarboxylic acid bridging two intermediates A. The reaction is activated at 0°C and carried out at room temperature without heating and reflux. Taking advantage of the difference in reactivity between aliphatic primary alcohols and phenolic hydroxyl groups, combined with the steric sensitivity of acyl-DMAP intermediates to nucleophiles, the reaction occurs only on the sterically hindered and highly reactive aliphatic primary hydroxyl groups, while the phenolic hydroxyl groups do not participate in the reaction throughout the process.

[0019] (3) Under nitrogen protection, intermediate B was added to anhydrous dichloromethane, stirred and cooled to 0°C, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDCI), 1-hydroxybenzotriazole (HOBt) and triethylamine were added, and the mixture was stirred and activated for 10-30 min. After adding 4-penten-1-amine, the mixture was restored to room temperature and stirred for 10-16 h. After the reaction was completed, the organic phase was washed once with dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated brine solution, respectively. After drying with anhydrous sodium sulfate, the mixture was filtered. The solvent was removed by rotary evaporation of the filtrate, and the crude product was recrystallized twice in anhydrous ethanol to obtain the bifunctional monomer BZT-BN. The chemical reaction equation is as follows:

[0020] This step involves an amidation reaction catalyzed by EDCI / HOBt. EDCI first reacts with the free carboxyl group of intermediate B to generate an O-acylisourea intermediate. HOBt then rapidly reacts with it to convert into a stable HOBt active ester. Triethylamine acts as an acid-binding agent to neutralize the hydrochloric acid generated in the reaction, maintaining the weak basicity of the system. The primary amino group of 4-penten-1-amine acts as a nucleophile to attack the acyl carbon atom of the HOBt active ester, generating an amide bond through addition-elimination and releasing HOBt. The introduction of HOBt not only improves the reactivity but also prevents the racemization of the axial chirality of binaphthol by generating a sterically hindered active ester. The nucleophilicity of the primary amino group is much higher than that of the phenolic hydroxyl group, and the reaction is carried out at room temperature, ensuring that the reaction only occurs between the carboxyl and amino groups, while the phenolic hydroxyl group remains intact. The low-temperature reaction conditions and the design of the system without free radical initiators effectively avoid the premature thermal self-polymerization of the terminal alkenyl group, preserving all active sites for subsequent photocrosslinking.

[0021] Preferably, the alkyl diol in (1) is selected from 1,4-butanediol, 1,6-hexanediol or 1,8-octanediol.

[0022] Preferably, in (1), the molar ratio of 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, alkyl diol and potassium carbonate is 1:8-12:2.5-3.5.

[0023] Preferably, in (1), 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, N,N-dimethylformamide and deionized water are in a mass ratio of 1:5-8:10-20.

[0024] Preferably, the concentration of dilute hydrochloric acid in (1) is 0.1-0.5 mol / L.

[0025] Preferably, the volume ratio of ethyl acetate to petroleum ether in the ethyl acetate / petroleum ether mixed solvent in (1) is 1:3.

[0026] Preferably, the molar ratio of (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthyl, N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and intermediate A in (2) is 2:2.2-2.5:0.2-0.3:1.

[0027] Preferably, in (2), (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthylene and dichloromethane are in a mass ratio of 1:10-15.

[0028] Preferably, the concentration of the dichloromethane solution of intermediate A in (2) is 10-15 wt%.

[0029] Preferably, the concentration of dilute hydrochloric acid in (2) is 0.1-0.5 mol / L.

[0030] Preferably, in the gradient elution step (2), the volume ratio of ethyl acetate to petroleum ether in each step of the elution gradually increases from 0:1 to 1:1.

[0031] Preferably, in (3), intermediate B, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole, triethylamine and 4-pentene-1-amine are in a molar ratio of 1:1.2-1.5:0.1-0.15:0.15-0.3:1-1.2.

[0032] Preferably, in step (3), the mass ratio of intermediate B to anhydrous dichloromethane is 1:8-15. Preferably, the concentration of dilute hydrochloric acid in step (3) is 0.1-0.5 mol / L.

[0033] Furthermore, the present invention also provides a method for preparing a high-resolution ultraviolet-infrared dual-barrier polyester protective film, comprising the following steps:

[0034] S1. After the dried polyethylene terephthalate resin, polybutylene terephthalate resin, bifunctional monomer BZT-BN, heat stabilizer and antioxidant are mixed evenly, they are added to the main feed port of the twin-screw extruder. The ultraviolet photoinitiator is added to the side feed port of the 10th section of the extruder and melt extrusion is carried out to obtain the extruded melt.

[0035] S2. The extruded melt is rapidly cooled and formed by a casting roller at 30-40℃ to obtain an amorphous thick sheet;

[0036] S3. After preheating the amorphous thick sheet at 80-95℃, stretch it longitudinally by 3.0-3.5 times, and then after preheating it at 95-115℃, stretch it transversely by 3.0-3.5 times to obtain a film;

[0037] S4. First, heat the film at 180-220℃ for 5-10 seconds, then cool it down to 60-80℃ at a rate of 10-20℃ / second, hold for 4-8 seconds, keep the film temperature at 60-80℃, irradiate it under ultraviolet light for 10-30 seconds, and finally cool it to room temperature and roll it up to obtain a high-definition ultraviolet and infrared double-barrier polyester protective film.

[0038] Preferably, the length-to-diameter ratio of the twin-screw extruder in S1 is 40:1.

[0039] Preferably, in S1, the temperature of the twin-screw extruder is 240-250℃ for the first to third stages, 260-270℃ for the fourth to ninth stages, 260℃ for the tenth stage, 255-265℃ for the die head, and 200-240 rpm for the screw speed.

[0040] Preferably, the thickness of the amorphous sheet in S2 is 150-300 μm.

[0041] Preferably, the wavelength of the ultraviolet light in S4 is 365 nm and the irradiance is 50-150 mW / cm². 2 .

[0042] Preferably, the mechanism of action of the high-definition ultraviolet-infrared dual-barrier polyester protective film of the present invention is explained as follows:

[0043] The bifunctional monomer BZT-BN of this invention has three functional units connected by covalent bonds in its molecular structure, avoiding the phase separation, migration, precipitation, and functional mismatch problems of multi-component physical mixtures. The phenolic hydroxyl group retained in the benzotriazole unit can achieve ultraviolet absorption through intramolecular proton transfer and can also act as a temperature-responsive switch to regulate conformation through reversible changes in hydrogen bonds; the binatol chiral center serves as the inducing core of the cholesteric helix, and its axial chirality is preserved during synthesis and processing through the control of catalysts and reaction conditions; the terminal alkenyl group serves as a crosslinking site, providing reactivity for the permanent locking of the subsequent helical structure. The three components achieve functional synergy at the molecular level, laying the structural foundation for the comprehensive performance of the film.

[0044] During film preparation, the molecular framework of BZT-BN consists of biphenyl ester, hexamethylene flexible chains, and benzotriazole units. Its ester bonds and aromatic structures are highly similar to those of PET and PBT, respectively. Based on the principle of similar solubility parameters in polymer physics, the solubility parameters of BZT-BN are close to those of PET and PBT, exhibiting good thermodynamic compatibility and preventing macroscopic phase separation. Molecular-level uniform dispersion is achieved during the melt blending stage, without agglomeration or phase separation. During biaxial stretching, BZT-BN molecules orient along the stretching direction, and the chiral center of binatol induces the spontaneous assembly of surrounding molecules to form a preliminary cholesteric helical structure. The gradient cooling heat setting stage is crucial for structure regulation. Utilizing the difference in thermal expansion coefficients between the PET / PBT matrix and the BZT-BN components, the structure is further refined in thin films. A continuous stress gradient is formed along the film thickness direction, which induces a gradient distribution of pitch from the surface to the core, broadening the effective bandwidth of infrared reflection. At the same time, as the temperature gradually decreases, the intramolecular hydrogen bonds of the benzotriazole unit are gradually restored, establishing an initial conformation and helical torsion force state corresponding to the temperature. In the subsequent ultraviolet light crosslinking stage, the high-boiling-point photoinitiator TPO introduced through side feeding decomposes under 365nm ultraviolet light to generate free radicals, initiating mild free radical polymerization of the BZT-BN terminal alkenyl groups to form a three-dimensional crosslinked network. This fixes the helical orientation and pitch gradient formed during stretching and heat setting. The mild crosslinking design ensures the long-term stability of the structure without restricting the local conformational movement of the benzotriazole unit, thus preserving the necessary molecular degrees of freedom for the thermo-adaptive function.

[0045] The high efficiency of the film in blocking ultraviolet light originates from the intramolecular proton transfer (ESIPT) effect of the benzotriazole unit: when irradiated by ultraviolet light in the 280-400nm range, the phenolic hydroxyl group on the benzotriazole absorbs photon energy, and the hydrogen atom transfers to the adjacent nitrogen atom to form an excited-state tautomer. Subsequently, the energy is dissipated as heat through nonradiative transitions, and the benzotriazole returns to the ground state. The whole process is reversible and does not destroy the molecular structure. Unlike physically added small molecule ultraviolet absorbers, the benzotriazole unit in this invention is integrated into the cross-linked network through covalent bonds, and will not migrate, precipitate or be lost due to photodegradation, which greatly improves the service life of the film.

[0046] The infrared reflection function of the thin film is based on the Bragg reflection effect of the cholesteric liquid crystal, and its reflection center wavelength satisfies λ=n·P (n is the average refractive index of the system, and P is the pitch of the cholesteric helix). The gradient pitch distribution realizes wide-band coverage of the near-infrared band. Its thermo-adaptive properties originate from the temperature-induced reversible changes in the intramolecular hydrogen bonds of benzotriazole: at room temperature, the phenolic hydroxyl group of benzotriazole forms a stable six-membered ring intramolecular hydrogen bond with the adjacent nitrogen atom, maintaining a specific planar conformation of the benzotriazole unit. This conformation is transmitted to the chiral center of binaphthol through covalent ester bonds, maintaining a fixed dihedral angle and helical twisting force, corresponding to a determined pitch and reflection wavelength. When the ambient temperature rises, the molecular thermal motion intensifies, the intramolecular hydrogen bonds gradually break, and the benzotriazole unit undergoes conformational torsion. This change is directly transmitted to the binaphthol core through ester bonds, altering its chiral environment and helical twisting force. According to the relationship between pitch and twisting force P=2π / β, a decrease in helical twisting force leads to an increase in pitch, a redshift of the reflection center wavelength towards longer wavelengths, and a simultaneous increase in near-infrared reflectivity. When the temperature decreases, the intramolecular hydrogen bonds reform, the conformation of benzotriazole and binaphthol is restored, and the pitch and reflection wavelength are restored, thus achieving a zero-energy adaptive thermal management function with high temperature and high reflectivity and low temperature and high transmittance.

[0047] The high-definition properties of the thin film stem from molecular-level functional dispersion and interface matching: First, BZT-BN is a molecular-level functional unit, lacking the aggregates and light scattering centers found in inorganic nanoparticle doping systems, as well as the microphase separation structure of multi-component physical mixing; second, the abundant ester bonds, ether bonds, and aromatic ring structures in the BZT-BN molecule ensure a high degree of refractive index matching with the PET / PBT matrix, resulting in minimal interfacial reflection loss; under the combined effect of multiple factors, high transparency and ultra-low haze are achieved, meeting the high-definition optical requirements of the architectural and automotive fields.

[0048] Compared with the prior art, the beneficial effects of the present invention are:

[0049] 1. This invention covalently integrates the benzotriazole UV-absorbing group, the binatol chiral center, and the polymerizable double bond into the same molecular framework to form the bifunctional monomer BZT-BN. This avoids the inherent phase separation, migration, and functional mismatch problems in existing multi-component physical mixing systems containing UV absorbers, chiral dopants, and polymerizable monomers. The molecular structure of BZT-BN exhibits good thermodynamic compatibility with the PET / PBT matrix, achieving uniform molecular-level dispersion during melt blending. This ensures both the uniform distribution of UV-absorbing groups and chiral centers along the film thickness direction and avoids the formation of light scattering centers by agglomerates in inorganic nanoparticle doping systems. This provides a molecular-level structural guarantee for achieving a balance between high resolution and dual barrier functions.

[0050] 2. This invention utilizes the temperature-dependent reversible breakdown of intramolecular hydrogen bonds in benzotriazole units to drive changes in the helical twisting force of the binatol chiral center, achieving zero-energy thermo-adaptive infrared reflection in a PET film system without the need for external energy or a sensor control system. As the ambient temperature rises, the intramolecular hydrogen bonds gradually break, causing conformational torsion of the benzotriazole. This change is transmitted to the binatol core via covalent ester bonds, altering its helical twisting force. The increased pitch causes a redshift of the reflection center wavelength towards longer wavelengths, automatically increasing near-infrared reflectivity. When the temperature decreases, the hydrogen bonds reform, and the pitch and reflection wavelength return to their initial state. This intramolecular synergistic mechanism allows the film to automatically adjust its infrared reflection performance according to changes in ambient temperature, effectively reducing building cooling and heating energy consumption, while avoiding the dependence on external power sources and control systems found in existing electrochromic or thermochromic smart windows.

[0051] 3. This invention utilizes the polymerizable double bonds in the BZT-BN molecule to form a three-dimensional polymer network through ultraviolet light crosslinking after film heat setting. This permanently locks the cholesteric phase helical orientation and pitch gradient structure formed during biaxial stretching and gradient cooling heat setting. Simultaneously, the covalently bonded benzotriazole units are fixed within the crosslinked network and cannot migrate or precipitate, significantly improving the long-term stability and weather resistance of the film. Compared to existing coated cholesteric phase liquid crystal infrared reflective films, the functional components of this invention are dispersed at the molecular level within the PET matrix, fundamentally avoiding adhesion degradation and scratch / detachment problems caused by insufficient interfacial bonding between the coating and the substrate, thus ensuring long-lasting ultraviolet blocking and infrared reflection performance.

[0052] 4. This invention achieves a balance between high transmittance in the visible light region and wide-band reflection in the near-infrared region through the synergistic design of a PET / PBT blend matrix and in-situ control of the pitch gradient distribution of the cholesteric liquid crystal via a gradient cooling heat setting process, without the need for multi-layer co-extrusion or complex coating processes. The introduction of the PBT component improves the crystallization behavior and dimensional stability of the matrix, while the good refractive index matching between PET and BZT-BN molecules effectively suppresses interfacial light scattering. This results in a film with both ultra-low haze and excellent visible light transmittance, meeting the stringent requirements for high-definition optical quality in fields such as building energy-saving window films and automotive heat insulation films, and possessing broad prospects for industrial application. Attached Figure Description

[0053] Figure 1 The intermediate A prepared in Example 2 of this invention 1 H NMR spectrum;

[0054] Figure 2 The intermediate B prepared in Example 2 of this invention 1 H NMR spectrum;

[0055] Figure 3 The bifunctional monomer BZT-BN prepared in Example 2 of this invention 1 H NMR spectrum. Detailed Implementation

[0056] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0057] Preparation Example 1: The specific preparation method of the bifunctional monomer BZT-BN includes the following steps:

[0058] (1) Under nitrogen protection, 0.1 mol (30.42 g) of 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, 0.8 mol of 1,4-butanediol and 0.25 mol of potassium carbonate were added to 152.1 g of N,N-dimethylformamide. The mixture was heated to 70 °C with stirring and reacted for 4 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filtrate was added to 304.2 g of deionized water and extracted three times with ethyl acetate. The organic phases were combined and washed once each with 0.1 mol / L dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated brine. After drying with anhydrous sodium sulfate, the mixture was filtered and the solvent was removed by rotary evaporation. The excess 1,4-butanediol was recovered by vacuum distillation. The crude product was recrystallized in a mixed solvent of ethyl acetate and petroleum ether (the volume ratio of ethyl acetate and petroleum ether was 1:3) to obtain intermediate A.

[0059] (2) Under nitrogen protection, 0.2 mol (80.48 g) (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthylene was added to 804.8 g of dichloromethane, stirred and cooled to 0 °C, 0.22 mol N,N'-dicyclohexylcarbodiimide and 0.02 mol 4-dimethylaminopyridine were added, stirred and activated for 20 min, and then a dichloromethane solution containing 0.1 mol of intermediate A with a concentration of 10 wt% was added dropwise. After the addition was completed, the temperature was restored to room temperature, and the reaction was stirred for 12 h. After the reaction was completed, the mixture was filtered, and the filtrate was washed once with dilute hydrochloric acid with a concentration of 0.1 mol / L, saturated sodium bicarbonate solution and saturated saline solution, dried with anhydrous sodium sulfate, filtered, and the solvent was removed by rotary evaporation. The crude product was purified by silica gel column chromatography using gradient elution. The volume ratio of ethyl acetate to petroleum ether in each eluent was gradually increased from 0:1 to 1:1 to obtain intermediate B.

[0060] (3) Under nitrogen protection, 0.1 mol (69.77 g) of intermediate B was added to 558.16 g of anhydrous dichloromethane, stirred and cooled to 0 °C, 0.12 mol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.01 mol of 1-hydroxybenzotriazole and 0.015 mol of triethylamine were added, stirred and activated for 10 min, 0.1 mol of 4-penten-1-amine was added and the mixture was restored to room temperature and stirred for 10 h. After the reaction was completed, the organic phase was washed once with dilute hydrochloric acid with a concentration of 0.1 mol / L, saturated sodium bicarbonate solution and saturated brine solution, respectively. After drying with anhydrous sodium sulfate, the mixture was filtered, and the solvent was removed by rotary evaporation. The crude product was recrystallized twice in anhydrous ethanol to obtain the bifunctional monomer BZT-BN.

[0061] Preparation Example 2: The specific preparation method of the bifunctional monomer BZT-BN includes the following steps:

[0062] (1) Under nitrogen protection, 0.1 mol (30.42 g) of 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, 1 mol of 1,6-hexanediol and 0.3 mol of potassium carbonate were added to 170 g of N,N-dimethylformamide. The mixture was heated to 75 °C with stirring and reacted for 5 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filtrate was added to 450 g of deionized water and extracted three times with ethyl acetate. The organic phases were combined and washed once each with 0.3 mol / L dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated brine. After drying with anhydrous sodium sulfate, the mixture was filtered and the solvent was removed by rotary evaporation. The excess 1,6-hexanediol was recovered by vacuum distillation. The crude product was recrystallized in a mixed solvent of ethyl acetate and petroleum ether (the volume ratio of ethyl acetate and petroleum ether was 1:3) to obtain intermediate A.

[0063] (2) Under nitrogen protection, 0.2 mol (80.48 g) (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthylene was added to 960 g of dichloromethane, stirred and cooled to 0 °C, 0.24 mol N,N'-dicyclohexylcarbodiimide and 0.025 mol 4-dimethylaminopyridine were added, stirred and activated for 30 min, and then a dichloromethane solution containing 0.1 mol of intermediate A with a concentration of 12 wt% was added dropwise. After the addition was completed, the temperature was restored to room temperature, and the reaction was stirred for 16 h. After the reaction was completed, the mixture was filtered, and the filtrate was washed once with dilute hydrochloric acid with a concentration of 0.3 mol / L, saturated sodium bicarbonate solution and saturated saline solution, dried with anhydrous sodium sulfate, filtered, and the solvent was removed by rotary evaporation. The crude product was purified by silica gel column chromatography using gradient elution. The volume ratio of ethyl acetate to petroleum ether in each eluent was gradually increased from 0:1 to 1:1 to obtain intermediate B.

[0064] (3) Under nitrogen protection, 0.1 mol (72.58 g) of intermediate B was added to 870 g of anhydrous dichloromethane, stirred and cooled to 0 °C, 0.135 mol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.012 mol of 1-hydroxybenzotriazole and 0.022 mol of triethylamine were added, stirred and activated for 20 min, 0.11 mol of 4-penten-1-amine was added and then the mixture was restored to room temperature and stirred for 12 h. After the reaction was completed, the organic phase was washed once with dilute hydrochloric acid with a concentration of 0.3 mol / L, saturated sodium bicarbonate solution and saturated brine solution, respectively. After drying with anhydrous sodium sulfate, the mixture was filtered, and the solvent was removed by rotary evaporation. The crude product was recrystallized twice in anhydrous ethanol to obtain the bifunctional monomer BZT-BN.

[0065] Preparation Example 3: The specific preparation method of the bifunctional monomer BZT-BN includes the following steps:

[0066] (1) Under nitrogen protection, 0.1 mol (30.42 g) of 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, 1.2 mol of 1,8-octanediol and 0.35 mol of potassium carbonate were added to 243.36 g of N,N-dimethylformamide. The mixture was heated to 80 °C with stirring and reacted for 6 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filtrate was added to 608.4 g of deionized water and extracted three times with ethyl acetate. The organic phases were combined and washed once each with 0.5 mol / L dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated brine. After drying with anhydrous sodium sulfate, the mixture was filtered and the solvent was removed by rotary evaporation. The excess 1,8-octanediol was recovered by vacuum distillation. The crude product was recrystallized in a mixed solvent of ethyl acetate and petroleum ether (the volume ratio of ethyl acetate and petroleum ether was 1:3) to obtain intermediate A.

[0067] (2) Under nitrogen protection, 0.2 mol (80.48 g) (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthylene was added to 1.2 kg of dichloromethane, stirred and cooled to 0 °C, 0.25 mol N,N'-dicyclohexylcarbodiimide and 0.03 mol 4-dimethylaminopyridine were added, stirred and activated for 40 min, and then a dichloromethane solution containing 0.1 mol of intermediate A at a concentration of 15 wt% was added dropwise. After the addition was completed, the mixture was brought back to room temperature and stirred for 20 h. After the reaction was completed, the mixture was filtered, and the filtrate was washed once with 0.5 mol / L dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated saline solution. After drying with anhydrous sodium sulfate, the mixture was filtered, and the solvent was removed by rotary evaporation. The crude product was purified by silica gel column chromatography using gradient elution. The volume ratio of ethyl acetate to petroleum ether in each eluent was gradually increased from 0:1 to 1:1 to obtain intermediate B.

[0068] (3) Under nitrogen protection, 0.1 mol (75.39 g) of intermediate B was added to 1.13 kg of anhydrous dichloromethane, stirred and cooled to 0 °C, 0.15 mol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.015 mol of 1-hydroxybenzotriazole and 0.03 mol of triethylamine were added, stirred and activated for 30 min, 0.12 mol of 4-penten-1-amine was added and then the mixture was restored to room temperature and stirred for 16 h. After the reaction was completed, the organic phase was washed once with dilute hydrochloric acid with a concentration of 0.5 mol / L, saturated sodium bicarbonate solution and saturated brine solution, respectively. After drying with anhydrous sodium sulfate, the mixture was filtered, and the solvent was removed by rotary evaporation. The crude product was recrystallized twice in anhydrous ethanol to obtain the bifunctional monomer BZT-BN.

[0069] Comparative Preparation Example 1: The difference between Comparative Preparation Example 1 and Preparation Example 2 is that 1,6-hexanediol is replaced with ethylene glycol.

[0070] Comparative Preparation Example 2: The difference between Comparative Preparation Example 2 and Preparation Example 2 is that 1,6-hexanediol is replaced with 1,12-dodecanediol.

[0071] Comparative preparation example 3: The difference between comparative preparation example 3 and preparation example 2 is that step (3) is omitted, and the remaining steps are the same as in preparation example 2.

[0072] Example 1: A specific method for preparing a high-definition ultraviolet-infrared dual-barrier polyester protective film, comprising the following steps:

[0073] S1. 700g of dried polyethylene terephthalate resin (intrinsic viscosity 0.65dL / g), 50g of polyethylene terephthalate resin (intrinsic viscosity 0.8dL / g), 20g of bifunctional monomer BZT-BN prepared according to Preparation Example 1, 0.5g of tris(2,4-di-tert-butylphenyl) phosphite, and 0.5g of antioxidant (a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) were mixed evenly and added to the main feed port of a twin-screw extruder. 0.5g of TPO was added to the side feed port of the 10th section of the extruder. The length-to-diameter ratio of the twin-screw extruder was 40:1. The temperature of the first to third sections of the extruder was 240℃, the temperature of the fourth to ninth sections was 260℃, the temperature of the tenth section was 260℃, the die temperature was 255℃, and the screw speed was 200rpm. Melt extrusion was performed to obtain the extruded melt.

[0074] S2. The extruded melt is rapidly cooled and formed by a 30°C casting roller to obtain an amorphous sheet with a thickness of 150μm;

[0075] S3. After preheating the amorphous thick sheet at 80°C, stretch it longitudinally by 3.0 times, and then after preheating it at 95°C, stretch it transversely by 3.0 times to obtain a film;

[0076] S4. First, heat the film at 180℃ for 5 seconds, then cool it down to 60℃ at a rate of 10℃ / second, hold for 4 seconds, and maintain the film temperature at 60℃. Then, irradiate the film at a wavelength of 365nm with an intensity of 50mW / cm². 2 Irradiated with ultraviolet light for 30 seconds, and then cooled to room temperature before being rolled up to obtain a high-definition ultraviolet and infrared dual-barrier polyester protective film.

[0077] Example 2: A specific method for preparing a high-definition ultraviolet-infrared dual-barrier polyester protective film, comprising the following steps:

[0078] S1. 800g of dried polyethylene terephthalate resin (intrinsic viscosity 0.70dL / g), 120g of polyethylene terephthalate resin (intrinsic viscosity 1.0dL / g), 60g of bifunctional monomer BZT-BN prepared according to Preparation Example 2, 1.5g of tris(2,4-di-tert-butylphenyl) phosphite, and 0.8g of antioxidant (a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) were mixed evenly and added to the main feed port of a twin-screw extruder. 1.2g of TPO was added to the side feed port of the 10th section of the extruder. The length-to-diameter ratio of the twin-screw extruder was 40:1. The temperature of the first to third sections of the extruder was 245℃, the temperature of the fourth to ninth sections was 265℃, the temperature of the tenth section was 260℃, the die temperature was 260℃, and the screw speed was 220rpm. Melt extrusion was performed to obtain the extruded melt.

[0079] S2. The extruded melt is rapidly cooled and formed by a 35°C casting roller to obtain an amorphous sheet with a thickness of 220μm;

[0080] S3. After preheating the amorphous thick sheet at 90°C, stretch it longitudinally by 3.2 times, and then after preheating it at 105°C, stretch it transversely by 3.2 times to obtain a film;

[0081] S4. First, heat the film at 200℃ for 8 seconds, then cool it down to 70℃ at a rate of 15℃ / second, hold for 6 seconds, and maintain the film temperature at 70℃. Then, irradiate the film at a wavelength of 365nm with an intensity of 120mW / cm². 2 Irradiated with ultraviolet light for 20 seconds, and then cooled to room temperature before being rolled up to obtain a high-definition ultraviolet and infrared dual-barrier polyester protective film.

[0082] Example 3: A specific method for preparing a high-definition ultraviolet-infrared dual-barrier polyester protective film, comprising the following steps:

[0083] S1. 900g of dried polyethylene terephthalate resin (intrinsic viscosity 0.75dL / g), 200g of polyethylene terephthalate resin (intrinsic viscosity 1.2dL / g), 100g of bifunctional monomer BZT-BN prepared according to Preparation Example 3, 3g of tris(2,4-di-tert-butylphenyl) phosphite, and 1g of antioxidant (a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) were mixed evenly and added to the main feed port of a twin-screw extruder. 2g of TPO was added to the side feed port of the 10th section of the extruder. The length-to-diameter ratio of the twin-screw extruder was 40:1. The temperature of the first to third sections of the extruder was 250℃, the temperature of the fourth to ninth sections was 270℃, the temperature of the tenth section was 260℃, the die temperature was 265℃, and the screw speed was 240rpm. Melt extrusion was performed to obtain the extruded melt.

[0084] S2. The extruded melt is rapidly cooled and formed by a 40°C casting roller to obtain an amorphous sheet with a thickness of 300μm;

[0085] S3. After preheating the amorphous thick sheet at 95°C, stretch it longitudinally by 3.5 times, and then after preheating it at 115°C, stretch it transversely by 3.5 times to obtain a film;

[0086] S4. First, heat the film at 220℃ for 10 seconds, then cool it down to 80℃ at a rate of 20℃ / second, hold for 8 seconds, and maintain the film temperature at 80℃. Then, irradiate the film at a wavelength of 365nm with an intensity of 150mW / cm². 2 Irradiated with ultraviolet light for 30 seconds, and then cooled to room temperature before being rolled up to obtain a high-definition ultraviolet and infrared dual-barrier polyester protective film.

[0087] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the bifunctional monomer BZT-BN is not added, the amount of PET resin is adjusted to 860g, the UV photoinitiator TPO is not added, and other components and process parameters are the same as in Example 2.

[0088] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the bifunctional monomer BZT-BN is not added. Instead, 60g of a physical mixture (composed of 30g of 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, 20g of (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthyl and 10g of 4-penten-1-amine) is added. The other components and process parameters are the same as in Example 2.

[0089] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that BZT-BN bifunctional monomer and photoinitiator TPO are not added. Instead, they are replaced with 30g of nano-ATO and 30g of 2-(2H-benzotriazol-2-yl)-4-methylphenol (UV-P). The total amount added is 60g, which is the same as the amount of BZT-BN in Example 2. The other components and their amounts remain unchanged.

[0090] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the bifunctional monomer BZT-BN prepared according to Preparation Example 2 is replaced with the bifunctional monomer BZT-BN prepared according to Comparative Preparation Example 1.

[0091] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that the bifunctional monomer BZT-BN prepared according to Preparation Example 2 is replaced with the bifunctional monomer BZT-BN prepared according to Comparative Preparation Example 2.

[0092] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that the bifunctional monomer BZT-BN prepared according to Preparation Example 2 is replaced with the bifunctional monomer BZT-BN prepared according to Comparative Preparation Example 3.

[0093] Performance testing:

[0094] 1. Visible light transmittance and haze: According to GB / T 2410-2008 standard, the transmittance and haze of the film were measured in the visible light range of 380-780nm using a WGT-S type transmittance / haze meter;

[0095] 2. Ultraviolet blocking rate: According to GB / T 2680-2021 standard, the ultraviolet transmittance of the film was measured in the ultraviolet light range of 280-400nm using a UV-2600 ultraviolet-visible spectrophotometer. The ultraviolet blocking rate (%) was calculated as 100% - ultraviolet transmittance (%).

[0096] 3. Near-infrared reflectance and thermo-adaptive properties: Using a Lambda 950 UV-Vis-NIR spectrophotometer with an integrating sphere attachment, the thin film sample was placed in a constant-temperature sample cell and kept at 25℃ and 60℃ for 10 min, respectively. The reflectance spectrum in the 780-2500 nm band was then measured, and the average reflectance and center wavelength of the reflection peak in the 900-1500 nm band were recorded. The shift of the reflection peak was calculated.

[0097] 4. Weather resistance test: In accordance with GB / T 16422.3-2022 standard, a QUV / spray type accelerated ultraviolet aging tester was used, employing UVA-340 lamps with an irradiance of 0.89 W / m². 2 The sample was taken out after running at 340 nm for 4 hours under the following cycling conditions: 4 hours of light exposure at 60℃ and 4 hours of condensation at 50℃. The ultraviolet blocking rate and near-infrared reflectance were measured again after 1000 hours of continuous operation.

[0098] 5. Heat shrinkage rate: According to GB / T 13542.2-2009 standard, the film sample was heated at 80℃ for 30 min, and the longitudinal dimension change rate before and after heating was measured.

[0099] The experimental results are shown in Table 1.

[0100] Table 1 Performance Test Results

[0101] Note: Comparative Example 3 uses nano-ATO, whose infrared blocking mechanism is free carrier absorption, not Bragg reflection as described in this invention.

[0102] Data Analysis:

[0103] Based on the test data in Table 1, it can be seen that Examples 1-3 of the present invention exhibit excellent performance in all key performance indicators, with Example 2 showing the most outstanding overall performance. Example 2 achieved the highest level in visible light transmittance, while having the lowest haze, an ultraviolet blocking rate close to 99.2%, and excellent near-infrared reflectance at both room temperature and high temperature, exhibiting the largest reflection peak shift. Furthermore, it maintained the highest performance retention rate after 1000 hours of QUV aging, and its thermal shrinkage rate at 80℃ was also at an ideal level.

[0104] The superior overall performance of Example 2 is likely due to the hexamethylene flexible spacer group in its BZT-BN molecule. In cholesteric liquid crystal systems, the length of the flexible spacer group directly affects the mobility of molecular chain segments and the efficiency of chiral information transmission. When the spacer group is C6, the molecular chain maintains sufficient flexibility to allow the benzotriazole unit to undergo conformational torsion with temperature changes, and can efficiently transmit this conformational change to the binatol chiral center, thereby achieving the maximum change in helical torsion force and the shift of the reflection peak. Simultaneously, the C6 spacer group exhibits good compatibility with the PET / PBT matrix, achieving uniform molecular-level dispersion during melt blending. This avoids light scattering caused by macroscopic phase separation and ensures the orderly arrangement of the cholesteric helical structure. Furthermore, the crosslinking network formed by the C6 spacer group has a moderate crosslinking density, which is sufficiently robust to lock the helical structure and resist thermal relaxation and photo-oxidative damage during long-term use, without excessively restricting the local conformational movement of the benzotriazole unit, thus preserving the necessary molecular degrees of freedom for the thermo-adaptive function.

[0105] The performance of each comparative example was inferior to that of Example 2. Comparative Example 1 did not add any BZT-BN bifunctional monomer, so the film lacked both the ESIPT (Excited-State Intramolecular Proton Transfer) mechanism for UV absorption provided by the benzotriazole unit and the Bragg reflection generated by the cholesteric helical structure induced by the binatol chiral center, resulting in a near-complete loss of its UV blocking and infrared reflection functions. Comparative Example 2 used a physical mixture of three functional components instead of covalently bonded BZT-BN. Although the initial UV blocking rate and near-infrared reflectance were comparable to those of Example 2, the lack of covalent bonds between benzotriazole and binatol in the physical mixture system prevented the regulation of helical torsion force driven by intramolecular hydrogen bond temperature-induced changes, thus essentially eliminating the thermotropic adaptive function. More importantly, the physically mixed small-molecule benzotriazole was prone to migration to the surface, volatilization, and photodegradation under long-term UV irradiation, leading to severe performance degradation after aging. Comparative Example 3 used a physical mixture of nano-ATO and UV-P. ATO nanoparticles readily aggregated in the PET matrix, forming micron-sized aggregates. These aggregates, with sizes comparable to visible light wavelengths, produced strong Mie scattering, leading to a significant increase in haze and a marked decrease in transmittance. Simultaneously, ATO achieved infrared blocking through free carrier absorption (Drude effect), a type of absorption-based blocking mechanism. The film itself absorbed infrared energy and heated up, causing secondary thermal radiation and lacking any thermo-adaptive capability. Comparative Examples 4 and 5 used excessively short (C2) and excessively long (C12) flexible spacers, respectively. When the C2 spacer was too short, molecular chain movement was severely restricted, and the conformational change of benzotriazole could not be effectively transferred to the binatol chiral center, resulting in a significant decrease in thermo-responsive sensitivity. Furthermore, insufficient molecular flexibility led to poor compatibility with the PET matrix and reduced dispersion uniformity. When the C12 spacer group is too long, although the molecular chain segments have sufficient mobility, the excessively long flexible segments dilute the efficiency of chiral information transfer from the binaphthol core to the surrounding liquid crystal molecules. At the same time, the long alkyl chain also has poor compatibility with the PET matrix, resulting in lower thermo-responsive efficiency and optical performance than the C6 system. The BZT-BN molecule in Comparative Example 6 lacks polymerizable double bonds and cannot form a cross-linked network to lock the cholesteric helical structure during the UV curing stage. Therefore, although the initial UV blocking and infrared reflectance performance is comparable to that of Example 2, during long-term use (especially after QUV aging thermal cycling and UV irradiation), the unlocked helical structure gradually relaxes and its orientation decreases, resulting in a severe degradation of infrared reflectance performance after aging.

[0106] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high-definition ultraviolet-infrared dual-barrier polyester protective film, characterized in that, It comprises the following components by weight: polyethylene terephthalate resin: 70-90 parts, polybutylene terephthalate resin: 5-20 parts, bifunctional monomer BZT-BN: 2-10 parts, heat stabilizer: 0.05-0.3 parts, antioxidant: 0.05-0.1 parts, and ultraviolet photoinitiator: 0.05-0.2 parts; The preparation method of the bifunctional monomer BZT-BN includes the following steps: (1) Under nitrogen protection, 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, alkyl diol and potassium carbonate were added to N,N-dimethylformamide. The mixture was heated to 70-80℃ with stirring and reacted for 4-6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filtrate was added to deionized water. The mixture was extracted three times with ethyl acetate. The organic phases were combined and washed once each with dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated brine. After drying with anhydrous sodium sulfate, the mixture was filtered, the solvent was removed by rotary evaporation, and the excess alkyl diol was recovered by vacuum distillation. The crude product was recrystallized in a mixed solvent of ethyl acetate / petroleum ether to obtain intermediate A. (2) Under nitrogen protection, (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthylene was added to dichloromethane, stirred and cooled to 0°C, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added, and the mixture was stirred and activated for 20-40 min. Then, a dichloromethane solution of intermediate A was added dropwise. After the addition was complete, the mixture was brought back to room temperature and stirred for 12-20 h. After the reaction was completed, the mixture was filtered. The filtrate was washed once with dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated saline solution, dried with anhydrous sodium sulfate and filtered. The solvent was removed by rotary evaporation of the filtrate. The crude product was purified by silica gel column chromatography using gradient elution to obtain intermediate B. (3) Under nitrogen protection, intermediate B was added to anhydrous dichloromethane, stirred and cooled to 0°C, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole and triethylamine were added, and the mixture was stirred and activated for 10-30 min. After adding 4-penten-1-amine, the mixture was restored to room temperature and stirred for 10-16 h. After the reaction was completed, the organic phase was washed once with dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated brine solution. After drying with anhydrous sodium sulfate, the mixture was filtered. The solvent was removed by rotary evaporation of the filtrate. The crude product was recrystallized twice in anhydrous ethanol to obtain the bifunctional monomer BZT-BN.

2. The high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 1, characterized in that, The intrinsic viscosity of the polyethylene terephthalate resin is 0.65-0.75 dL / g; the intrinsic viscosity of the polybutylene terephthalate resin is 0.8-1.2 dL / g; the heat stabilizer is tris(2,4-di-tert-butylphenyl) phosphite; the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; and the ultraviolet photoinitiator is photoinitiator TPO.

3. The high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 1, characterized in that, The alkyl diol in (1) is selected from one of 1,4-butanediol, 1,6-hexanediol or 1,8-octanediol.

4. The high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 1, characterized in that, In (1), the molar ratio of 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, alkyl diol and potassium carbonate is 1:8-12:2.5-3.5; the mass ratio of 2-(2H-benzotriazol-2-yl)-4-(bromomethyl)phenol, N,N-dimethylformamide and deionized water is 1:5-8:10-20; the concentration of dilute hydrochloric acid is 0.1-0.5 mol / L; and the volume ratio of ethyl acetate and petroleum ether in the ethyl acetate / petroleum ether mixed solvent is 1:

3.

5. The high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 1, characterized in that, In step (2), the molar ratio of (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthyl, N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and intermediate A is 2:2.2-2.5:0.2-0.3:1; the mass ratio of (R)-2,2'-bis(carboxymethyloxy)-1,1'-binaphthyl and dichloromethane is 1:10-15; the concentration of the dichloromethane solution of intermediate A is 10-15wt%; the concentration of dilute hydrochloric acid is 0.1-0.5mol / L; and the volume ratio of ethyl acetate to petroleum ether in each step of the gradient elution gradually increases from 0:1 to 1:

1.

6. The high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 1, characterized in that, In (3), the molar ratio of intermediate B, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole, triethylamine and 4-penten-1-amine is 1:1.2-1.5:0.1-0.15:0.15-0.3:1-1.2; the mass ratio of intermediate B and anhydrous dichloromethane is 1:8-15; and the concentration of dilute hydrochloric acid is 0.1-0.5 mol / L.

7. The method for preparing a high-definition ultraviolet-infrared dual-barrier polyester protective film according to any one of claims 1-6, characterized in that, Includes the following steps: S1. After the dried polyethylene terephthalate resin, polybutylene terephthalate resin, bifunctional monomer BZT-BN, heat stabilizer and antioxidant are mixed evenly, they are added to the main feed port of the twin-screw extruder. The ultraviolet photoinitiator is added to the side feed port of the 10th section of the extruder and melt extrusion is carried out to obtain the extruded melt. S2. The extruded melt is rapidly cooled and formed by a casting roller at 30-40℃ to obtain an amorphous thick sheet; S3. After preheating the amorphous thick sheet at 80-95℃, stretch it longitudinally by 3.0-3.5 times, and then after preheating it at 95-115℃, stretch it transversely by 3.0-3.5 times to obtain a film; S4. First, heat the film at 180-220℃ for 5-10 seconds, then cool it down to 60-80℃ at a rate of 10-20℃ / second, hold for 4-8 seconds, keep the film temperature at 60-80℃, irradiate it under ultraviolet light for 10-30 seconds, and finally cool it to room temperature and roll it up to obtain a high-definition ultraviolet and infrared double-barrier polyester protective film.

8. The method for preparing the high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 7, characterized in that, The length-to-diameter ratio of the twin-screw extruder in S1 is 40:1; the temperature of the first to third stages of the twin-screw extruder is 240-250℃, the temperature of the fourth to ninth stages is 260-270℃, the temperature of the tenth stage is 260℃, the die temperature is 255-265℃, and the screw speed is 200-240 rpm.

9. The method for preparing the high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 7, characterized in that, The thickness of the amorphous sheet in S2 is 150-300 μm.

10. The method for preparing the high-definition ultraviolet-infrared dual-barrier polyester protective film according to claim 7, characterized in that, The ultraviolet light in S4 has a wavelength of 365 nm and an irradiance of 50-150 mW / cm². 2 .